Aloe vera gel coating aggravates superficial scald incidence in 'Starking' apples during low-temperature storage. (1st March 2021) - Liu, Heng; Liu, Shaohua; Du, Bingyang; Dong, Kuntian; Wang, Yong; Zhang, Yuanhu
Highlights: Aloe vera gel coating increases superficial scald in 'Starking' in cold storage. Antioxidant capacity of 'Starking' in cold storage reduced despite aloe vera gel. Aloe vera gel increased α-farnesene and conjugated triene in 'Starking'. Abstract: The effects of aloe vera ( Aloe vera (L.) Burm. f.) gel treatment on the incidence of superficial scald in 'Starking' apples ( Malus domestica Borkh. Var. Starking) during cold storage were studied. Apples were harvested at the pre-climacteric stage and treated with aloe vera gel. The treatment increased malondialdehyde content and membrane lipid damage. Furthermore, it inhibited the release of ethylene at the early stage but increased it in the later stage. The expression level of ACC synthase 1 ( MdACS1 ) also increased, and the antioxidant capacity in apples, particularly, catalase, peroxidase, and superoxide dismutase activities, all decreased, while concomitantly, the content of α-farnesene and its oxidation product, conjugated triene increased, thereby aggravating superficial scald incidence during storage at low temperature.